Integrasi Budaya Terhadap Kapabilitas Dan Keunggulan Kompetitif Berkelanjutan ( Sustainable Competitive Advantage) Usaha Kecil Dan Usaha Mikro Etnis Maluku Di Kota Ambon - Fenri. A. S. Tupamahu (Conference In Business, Accounting, And Management (CBAM), 2015)
This research was aimed at to analyse the direct and indirect effects of the cultural integration on the capability and the sustainable competitive excellence. This was an exploratory study, and the investigation applied the correlational study, with the quantitative approach, whileas the research model was survey. Sample taken through a non-probability sampling, and the selection of the sample  using judg- ment sampling. The amount of sample was 124 entrepreneurs. The data was ana- lysed by applying inferential statistics measure, namely the path analysis. The re- search result shows that the Moluccan culture has significant direct effect on the capability. And the cultural integration influences sustainable competitive excel- lence of the small-scale and micro businesses. Capability influences sustainable competitive excellence of the Moluccans small-scale and micro businesses. Capa- bility mediates the effects of cultural integration on sustainable competitive excel- lence.    Keywords: Culture, Capability, Sustainable competitive excellence.